2017
DOI: 10.1016/j.watres.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals removal and microbial community assessment in a continuous fungal treatment of non-sterile real hospital wastewater after a coagulation-flocculation pretreatment

Abstract: Hospital wastewaters are a main source of pharmaceutical active compounds, which are usually highly recalcitrant and can accumulate in surface and groundwater bodies. Fungal treatments can remove these contaminants prior to discharge, but real wastewater poses a problem to fungal survival due to 2 bacterial competition. This study successfully treated real non-spiked, nonsterile wastewater in a continuous fungal fluidized bed bioreactor coupled to a coagulation-flocculation pretreatment for 56 days. A control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 33 publications
2
40
0
2
Order By: Relevance
“…This is because bacterial contamination under non-sterile conditions can negatively affect the performance of whole-cell WRF [154,167]. Indeed, poor removal of CBZ has been reported in fungal bioreactors operated under non-sterile conditions as compared to sterile fungal bioreactors [168][169][170]. For instance, Nguyen et al [161] reported only 5% CBZ removal in a whole-cell fungal membrane bioreactor.…”
Section: White-rot Fungi and Their Extracellular Enzymesmentioning
confidence: 99%
“…This is because bacterial contamination under non-sterile conditions can negatively affect the performance of whole-cell WRF [154,167]. Indeed, poor removal of CBZ has been reported in fungal bioreactors operated under non-sterile conditions as compared to sterile fungal bioreactors [168][169][170]. For instance, Nguyen et al [161] reported only 5% CBZ removal in a whole-cell fungal membrane bioreactor.…”
Section: White-rot Fungi and Their Extracellular Enzymesmentioning
confidence: 99%
“…Conventional wastewater treatment technologies cannot always remove pharmaceutical substances efficiently [1]. In such cases, the pharmaceuticals are released into the environment where they negatively affect living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…For a MBR based on a mixed culture of bacteria and white-rot fungi, a moderate removal of CBZ and DF (20 and 40%, respectively) from synthetic wastewater has been reported [7]. Removal of DF (by more than 90%) and CBZ (in the range of 50-80%) from nonsterile hospital wastewater, upon application of T. versicolor in a continuous fluidized bed bioreactor coupled to a coagulation-flocculation pretreatment step, has also been described [11].…”
Section: Introductionmentioning
confidence: 99%